The Influence of God Consciousness and Religiosity in Coping with Anxiety at Workplace among Malaysian Muslim Professionals - Husni Mohd Radzi; Lilie Zahara Ramly; Sapora Sipon; Khatijah Othman (International Association of Computer Science and Information Technology (IACSIT) Press, 2024)
Anxiety is form of psychological condition that can cause serious harm to human mind and overall well being. Today’s stressful and highly demanding work setting has intensified the pressure and expectations felt by the professionals in Malaysia. The intensity of stress may affect general safety, health and even lifestyles or relationships of a normally working persons. There are some people who turn to God and religion as alternative to heal or cope with their psychological discomfort. Thus, this study was conducted to discuss the level of anxiety and other psychological discomforts experienced by group of Muslim working people in several sectors and examined how God consciousness and religiosity could influence as a mechanism to control their anxiety. The data was collected through random sampling of 38 working citizens of Malaysia from several working sectors. This study utilised two main instruments to measure the outcome: first, ‘Depression, Anxiety and Stress scale’ or ‘DASS’ to gauge the level of anxiety and ‘Brief Religious Coping’ (BRCOPE) to investigate religious coping performed by respondents in dealing with their anxiety.